Surfing the net for software engineering notes. - Doernhoefer, Mark (Software engineering notes.)
Remember the good old days when your computer science professor assigned you a programming task that required you to turn in the source code (usually FORTRAN) and a flowchart? You'd run off, code up the assignment, get it to run correctly, then go back and write up the flowchart to match the program. That's how most of us learned to design software.